Evaluation of the learning management system and its relationship in the perception of engineering students - Carlos Dávila-Ignacio; Orlando Ortega-Galicio; Guillermo Morales-Romero; Nicéforo Trinidad-Loli; Beatriz Caycho-Salas; Elizabeth Auqui-Ramos; César León-Velarde; Renan Auqui-Ramos; Richard Flores-Cáceres (International Journal of Evaluation and Research in Education (IJERE), 2022)
The objective of this study was to identify the results of the learning management system (LMS) functionality, and its relationship in the perception of electronic engineering students. The results serve as a basis for continuous improvement for the higher institution, because these systems are tools that have the purpose of improving the performance and retention of the student in the virtual teaching-learning process. Initially, the reliability of the data collected was determined using Cronbach's Alpha, obtaining a consistency coefficient of 0.868. After processing the data in the SPSS software, using the 5-level Likert scale, it was determined that the indicators that present a better perception are related to the design and ease of navigation. However, 21.4% do not fully agree with the functionality, due to the technical problems presented when downloading the study material. The effect generated by the optimal functionality of the LMS is 70.87% satisfaction in students. The Chi square test validated the cause-effect relationship, with a significance of 0.000, between the functionality of the LMS, on the perception of the students. It determined that the indicators with a greater relationship refer to design, availability (connectivity) and ease of communication and interaction with the teacher and their peers.